2010
DOI: 10.1016/j.molimm.2010.05.287
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal region of human NFATc2 binds cJun to synergistically activate interleukin-2 transcription

Abstract: At eukaryotic promoters, multi-faceted protein-protein and protein-DNA interactions can result in synergistic transcriptional activation. NFAT and AP-1 proteins induce interleukin-2 (IL-2) transcription in stimulated T cells, but the contributions of individual members of these activator families to synergistically activating IL-2 transcription is not known. To investigate the combinatorial regulation of IL-2 transcription we tested the ability of different combinations of NFATc2, NFATc1, cJun, and cFos to syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Such separable binding of NFAT family members has also been observed in human Jurkat cells stimulated with PMA and ionomycin (39). Only NFAT1 has a unique C-terminal domain, which is reported to function as a transactivation domain as well as an interaction domain with Jun (39, 40). This domain may contribute to the initial change at the Il2 promoter.…”
Section: Discussionmentioning
confidence: 73%
“…Such separable binding of NFAT family members has also been observed in human Jurkat cells stimulated with PMA and ionomycin (39). Only NFAT1 has a unique C-terminal domain, which is reported to function as a transactivation domain as well as an interaction domain with Jun (39, 40). This domain may contribute to the initial change at the Il2 promoter.…”
Section: Discussionmentioning
confidence: 73%
“…Other combinations of NFATc1, NFATc2, cJun, and cFos were unable to achieve high levels of synergistic activation. Moreover, we found that the C-terminal activation domain of NFATc2 (amino acids 688-921) is capable of directly binding cJun homodimers, but not cJun/cFos heterodimers (Nguyen et al, 2010). This C-terminal region of NFATc2 is required for IL-2 transcriptional synergy between NFATc2 and cJun in Jurkat cells.…”
Section: Introductionmentioning
confidence: 96%
“…There are five members of the NFAT family, with NFATc1 and NFATc2 being the primary members expressed in T cells (Lyakh et al, 1997). Upon T cell activation NFATc2 rapidly enters the nucleus and occupies the promoter region of the IL-2 gene, whereas NFATc1 is synthesized upon T cell stimulation, enters the nucleus, and binds the IL-2 promoter several hours later (Loh et al, 1996; Lyakh et al, 1997; Nguyen et al, 2010; Timmerman et al, 1996). NFATc1 and NFATc2 share similar overall structural motifs with the distinguishing feature being the presence of a C-terminal activation domain on NFATc2 (amino acids 688-921) that is absent from NFATc1 (Hogan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations